2015
DOI: 10.7249/rr1084
|View full text |Cite
|
Sign up to set email alerts
|

Health, wellbeing and productivity in the workplace: A Britain's Healthiest Company summary report

Abstract: R ® is a registered trademark.RAND Europe is an independent, not-for-profit policy research organisation that aims to improve policy and decisionmaking in the public interest through research and analysis. RAND's publications do not necessarily reflect the opinions of its research clients and sponsors. Limited Print and Electronic Distribution RightsThis document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 42 publications
1
39
1
1
Order By: Relevance
“…Healthcare workers caring for people with COVID-19 have commonly experienced discrimination, alongside people who have recovered from COVID-19, those in lower socioeconomic groups and those with particular religious or racial identities [ 52 ]. Rates of presenteeism (being at work in ill-health) are high in healthcare workers [ 19 ] and one of the main drivers of presenteeism is mental ill-health [ 53 ]. The emotional impacts of the COVID-19 pandemic are therefore likely to have significant financial and resource implications for organizations since the economic cost of presenteeism far outweighs that of absenteeism [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare workers caring for people with COVID-19 have commonly experienced discrimination, alongside people who have recovered from COVID-19, those in lower socioeconomic groups and those with particular religious or racial identities [ 52 ]. Rates of presenteeism (being at work in ill-health) are high in healthcare workers [ 19 ] and one of the main drivers of presenteeism is mental ill-health [ 53 ]. The emotional impacts of the COVID-19 pandemic are therefore likely to have significant financial and resource implications for organizations since the economic cost of presenteeism far outweighs that of absenteeism [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sense of contribution experienced by our participants appeared to be irrespective of whether they worked in a clinical or non-clinical role, or were physically present in the hospital setting during the first wave of the pandemic (e.g., some participants were remote working during this time, others had been shielding if they were clinically vulnerable, or had self-isolated at some point during the pandemic due to COVID-19 exposure). This has been recognized by hospital trusts and some employers provided guidance or recommendations for how to help staff who were unable to engage in their normal roles to contribute to the national effort, for example through non-clinical activities, and remote support [ 53 ]. However, it has been found that some healthcare workers unable to work on the frontline during the pandemic not only felt guilt, but perceived themselves to be undervalued, which demonstrates the importance of colleagues and managers in healthcare organizations proactively acknowledging their contribution to the pandemic response [ 57 ] to demonstrate inclusion and equity in recognition of effort.…”
Section: Discussionmentioning
confidence: 99%
“…Bringing many of these concepts together, a recent study by Hafner et al (2015) examines the links between health, well-being and productivity using the data from the 2014 Britain’s Healthiest Company competition. They look at the relationships between lost productivity (in terms of absenteeism and presenteeism) and three categories of health and well-being, namely, the job and work environment (e.g.…”
Section: The Costs Of Poor Well-being To Productivitymentioning
confidence: 99%
“…The authors of a study published by RAND (Hafner et al , 2015, p. ix) state that: “[…] simple economics tells us that companies only find it profitable to invest in health promotion programmes when the benefits outweigh the cost of investment in the longer term. For companies it is crucial to understand the direct link between wellbeing and productivity.…”
Section: A Significant Opportunity For Research-into-practicementioning
confidence: 99%
“…This study is modelled after Britain’s Healthiest Workplace [ 28 ] in partnership with RAND Europe. Ethics approval was obtained from the Universiti Kebangsaan Malaysia Research Ethics Committee (NN-2019-152).…”
Section: Methodsmentioning
confidence: 99%